Litoral e sertão : proximidades e distanciamentos na prática colaborativa interprofissional na Estratégia de Saúde da Família - Morais, Jonathan Cordeiro de (2024)
It is a research of a mixed approach of the cross-sectional, descriptive and analytical type, starting with the quantitative approach and then deepened through the qualitative approach. It was carried out in the Northeast region of Brazil, in the state of Paraíba, in two municipalities: a medium-sized one in the coastal region, and a small one, located in the hinterland of the state. A total of 68 health professionals participated in this research: Community Health Agents, Nurses, Dental Surgeons and Physicians, distributed in 17 Family Health Teams (FHS) in Primary Health Care (PHC). Quantitative data were collected using the Assessment of Interprofessional Team Collaboration Scale II (AITCS II) and analyzed using IBM SPSS® Statistics 21.0, which was considered significant to be less than 0.05. Qualitative data were collected through recorded interviews with the participants according to a semi-structured instrument. The speeches were recorded, transcribed and analyzed using the Atlas.ti software, the Collective Subject Discourse (CSD) technique proposed by Lefévre, Lefévre and Teixeira, and content analysis (CA). In the quantitative analysis, it is possible to perceive the weaknesses of the teams, highlighting the weaknesses in both municipalities, requiring immediate interventions and approaches to resolve conflicts. In the qualitative analysis, it is possible to perceive the fragility in the face of the mutual understanding of the different roles played by each professional and by the management, recognizing that the diversity of perspectives enriches the approach to health care, and it is necessary to apply research such as this one in the reality of other municipalities and health services. It is concluded that interprofessionality has shown promise for integrated health care, the reality shows challenges such as professional dissatisfaction due to poor coordination and communication between teams, requiring urgency to solve issues that affect the work environment.